A component method for moment-resistant glulam beam–column connections with glued-in steel rods. (15th May 2016) - Yang, Huifeng; Liu, Weiqing; Ren, Xiao
Graphical abstract: Highlights: Component method for moment-resistant timber connections with glued-in steel rods. Moment–rotation behavior of the ductile glulam beam-to-column connections. Equivalent components for steel box section connecting elements. Development of the theoretical model and evaluation using experimental results. Abstract: This paper presents an analytical method of the determination of the moment resistance, initial stiffness and the rotation capacity of glulam beam–column connections with glued-in rods. The methodology is based on the component method and is implemented using appropriate mechanical models. As a simplified component of the steel box sections, the substitute T-stub in the model is well verified by the experimental results, whether with or without the transverse web stiffeners. On the basis of the mechanical properties of the individual components such as initial stiffness, load resistance and a further force–deformation relationship, the moment–rotation curves of the entire joint can be obtained. The proposed model is evaluated against the experimental results, which shows good agreement between the two.